JUSTICE INTRODUCTION IN LAND LAW - syamsuddin pasamai (Law Faculty of Universitas Bandar Lampung, 2022)
Justice is one of the legal goals to be realized, while the existence of land is an essential human need whose regulations need to be regulated transparently in land law. This phenomenon, ex officio places land as an integral part of human rights that must be fulfilled for the benefit and certainty of other legal purposes. Therefore, the proposed